Solaris 8 : network administrator certification : training guide - Rehman, Rafeeq Ur (Training guide., 2001)
This book helps certified Solaris System Administrators pass the Network Administrator exam. This exam is rapidly increasing in popularity. This book follows the successful Training Guide format, which delivers superior solutions in the form of lab examples, self-assessment opportunities, summary tables, and several effective learning tools - including ExamGear -- that enhance the learning experience.